Economic cycle and deceleration of female labor force participation in Latin America - Serrano, Joaquín (2019)
We study the behavior of female labor force participation (LFP) over the business cycle by estimating fixed effects models at the country and population-group level, using data from harmonized national household surveys of 18 Latin American countries in the period 1987–2014. We find that female LFP follows a countercyclical pattern—especially in the case of married, with children and vulnerable women—which suggests the existence of an inverse added-worker effect. We argue that this factor may have contributed to the deceleration in female labor supply in Latin America that took place in the 2000s, a decade of unusual high economic growth.